Application of Time Token Learning to Improve Elementary Students' Communication Skills - Siti Amsarina Pangaribuan (Yayasan Zia Salsabila, 2023)
Students' skills in communicating teaching materials are still in the low category, so they need active learning strategies, one of which is time tokens. The purpose of this research is to find out the results of applying the time token learning strategy to elementary school-age children. This study used a qualitative research method with a descriptive approach. The results of this study are (1) children can improve their speaking skills more easily with the help of the time token strategy; and (2) children can express their opinions well, and listen to and respect the opinions of their peers.